Analisis Hambatan Samping Terhadap Tingkat Pelayanan Jalan Pada Ruas Jalan Ahmad Yani Kota Maumere - Yuniaty, Fortunata Rosalina; Karels, Dolly W.; Ramang, Ruslan (Universitas Nusa Cendana, 2023)
The increase in development in an area and the increase in population cause the need to pay attention to facilities and infrastructure in the field of transportation, especially roads. Maumere is the capital of the Sikka district. The increasing need of the people of Maumere City for traffic movement causes road performance to decrease because traffic movement exceeds the existing road capacity. Side friction occur on this road section because there are several offices, schools, shopping centers, and restaurants and are the route in and out of campuses, schools, shops, and markets. The purpose of the study is to determine the side friction of working days and holidays, the level of service of working days and holidays, and the effect of side friction on the level of road services. The method used in the research is quantitative based on PKJI 2014. The results of the weekday side friction analysis showed that the value of side friction reached 1,286 events/hour and included very high side friction classes and holidays showed that the side resistance factors reached 125 events/hour and included low side friction classes. The road service level value on weekdays is B and the holiday road service level value is B. The value of the side friction class on weekdays is high and the value of the road service level is B. while on holidays the value of the side friction class is very low and the value of the road service level is B.